The Potential of Giving Silage Feed Based on Corn Plant Waste (Zea mays) Using Local Microorganisms (Indigenous Microorganism) Against the Percentage of Non-Carcass on Local Sheep - Bahari Ryansyah Hasibuan; A H Daulay; Hasnudi; M Tafsin; Yunilas (Jurnal Peternakan Integratif, 2019)
This study aims to examine the effect of complete corn waste based on silagefeed on the percentage of non carcasses on local sheep. The study was conducted at theLaboratory of Animal Biology at the University of North Sumatra in May - August2018. The design used was a Completely Randomized Design (CRD) with 4 treatmentsand 3 replications using sheep with an average initial weight of 11.2 ± 0.4 kg. Thetreatments consisted of four levels of complete silage feed based on corn waste P1(20%), P2 (40%), P3 (60%), and P4 (80%).The parameters observed were: weight,head, foot, skin, tail, trachea and lungs, liver, heart, blood, and digestive tract.Theresults showed that complete feed based corn waste silage did not have a significanteffect (P> 0.05) on the percentage of non-carcass weight such as skin, tail, trachea andlungs, blood and digestive tract, but gave a non-significant effect on the percentage noncarcass weights such as head, feet, heart and liver. The conclusion of complete feedsilage based on corn waste can have a significant influence on the internal non carcass(liver and heart) and external (head and foot) parts of male local sheep. In addition itgives a non significant influence on the non-internal carcass parts (trachea and lungs,blood and digestion) and the external (skin and tail) of male local sheep.